TO BE OTENTIK: MENYIKAPI FENOMENA MASSA DALAM BERAGAMA ALA SOREN KIERKEGAARD - Daniel, Albertus; Hasibuan, Nelson (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Soren Kierkegaard stated that in order to know the truth, individuals in the masses must experience God personally or experience and realize subjective experiences, not just practical theoretical ones based on the encouragement of the masses. This research aims to determine Kierkegaard's perspective regarding being an authentic individual, even though he is among the masses, in this case using qualitative methods with a library research approach. The data in this research is descriptive, based on the collection of literature studies. The results of this research are that, just as mass phenomena cannot be avoided, they can be responded to properly so as not to be carried away by mass currents. 1) Mass currents are a manifestation of individuals who fail to touch the relationships of their subjective experiences, 2) Being authentic is harmony between actions and subjective relationships of individuals, 3) Appreciation of subjective relationships that are based on God will help to avoid various falsehoods and lead to the truth true.